Constitutional model for financial authority restructuring between central and regional governments in Indonesia - Muhammad Rizal; Sapto Hermawan (Institute Of computer Science (IOCS), 2026)
The imbalance of fiscal authority between Indonesia’s central and regional governments remains a fundamental issue that challenges the constitutional ideal of fiscal decentralization. Although the 1945 Constitution mandates regional autonomy, the concentration of financial control at the central level has led to inefficiencies, idle funds, and procedural disparities. This study examines the constitutional framework governing fiscal authority, identifies procedural challenges in its implementation, and proposes a constitutional model to restructure intergovernmental fiscal relations. Using a normative juridical approach combined with conceptual and statutory analysis, the research explores constitutional provisions, fiscal regulations, and Constitutional Court decisions to evaluate the alignment between law and practice. The findings reveal that the existing system remains hierarchically centralized and procedurally fragmented, limiting transparency, accountability, and regional fiscal innovation. Therefore, this article proposes a procedural constitutional model emphasizing coordination, equity, and efficiency as the foundation for a balanced fiscal relationship between the central and regional governments. This study introduces a novel constitutional procedural model to harmonize Indonesia’s central–regional fiscal governance through transparency and accountability. Such a model reinforces legal certainty while promoting an accountable and participatory fiscal governance system consistent with Indonesia’s constitutional democracy.